In search of WTO trade effects : preferential trade agreements promote trade strongly, but unevenly - Eicher, Theo S.; Henn, Christian, 1978- (IMF working paper, 2009)
The literature measuring the impact of Preferential Trade Agreements (PTA) and WTO membership on trade flows has produced remarkably diverse results. Rose's (2004) seminal paper reports a range of specifications that show no WTO effects, but Subramanian and Wei (2007) contend that he does not fully control for multilateral resistance (which could bias WTO estimates). Subramanian and Wei (2007) address multilateral resistance comprehensively to report strong WTO trade effects for industrialized countries but do not account for unobserved bilateral heterogeneity (which could inflate WTO estimates). We unify these two approaches by accounting for both multilateral resistance and unobserved bilateral heterogeneity, while also allowing for individual trade effects of PTAs. WTO effects vanish and remain insignificant throughout once multilateral resistance, unobserved bilateral heterogeneity, and individual PTA effects are introduced. The result is robust to the use of alternative definitions and coding conventions for WTO membership that have been employed by Rose (2004), Tomz et al. (2007), or by Subramanian and Wei's (2007).